Distinct clinico-genomic factors drive outcomes in patients with myelofibrosis and disease-related anemia - Ball, Somedeb; Al Ali, Najla H.; Jain, Akriti G.; Aguirre, Luis E.; Yun, Seongseok; Chan, Onyee; Xie, Zhuoer; Sallman, David A.; Lancet, Jeffrey; Padron, Eric; Komrokji, Rami S.; Kuykendall, Andrew T. (Frontiers in Hematology, 2024)
BackgroundDisease related anemia in myelofibrosis (MF) is common and prognostically detrimental. Anemia in MF poses a therapeutic challenge as it contributes to poor quality of life and often interferes with JAK inhibitor therapy. Still, the causes for anemia in MF are varied raising the question as to whether all patients with MF-related anemia should be viewed through the same prognostic lens.MethodsIn this retrospective study, we analyzed clinical and genomic data of patients with MF-related anemia using an institutional MF database. Anemia was defined as the requirement of red blood cell transfusions or a hemoglobin level of <10 g/dL at presentation. Multivariable analysis performed using Cox regression formed the basis of a proposed prognostic scoring system for patients with anemic MF.ResultsAmong 739 patients with MF, 365 (49.5%) were anemic at presentation. Anemic patients were older, had lower platelet count, lower serum albumin, and higher ferritin level than non-anemic patients. The presence of a JAK2 mutation was less common, whereas mutations in U2AF1 and EZH2 were enriched in the anemic cohort. Blast phase transformation was more common in anemic patients. After a median follow up of 34.5 months, median overall survival (OS) was significantly shorter in anemic vs. non-anemic MF (30.2 vs. 73.9 months; p<0.01). Leukocytosis, thrombocytopenia, low serum albumin, and the presence of a mutation involving SRSF2 or TP53 were independent predictors of inferior OS in anemic MF on multivariable analysis. A proposed prognostic model including these factors stratified anemic MF cohort into low, intermediate, and high-risk categories, with median OS of 69, 37.7, and 11.6 months, respectively (p <0.01).ConclusionsOur study highlights the heterogeneity of patients with MF and anemia and identifies key prognostic correlates in this subgroup. Our proposed model may help guide therapeutic decision-making in this high-risk cohort.